Gestational and lactational exposure to bisphenol AF in maternal rats increases testosterone levels in 23-day-old male offspring. (November 2016) - Li, Jing; Sheng, Nan; Cui, Ruina; Feng, Yixing; Shao, Bing; Guo, Xuejiang; Zhang, Hongxia; Dai, Jiayin
Abstract: During prenatal and postnatal development, exposure to environmental chemicals with estrogenic activity, such as bisphenol AF (BPAF), may result in reproductive disorders. Currently, the mechanisms behind such disorders in male offspring induced by gestational and lactational exposure to BPAF remain poorly understood. Here, female rats from gestational day (GD) 3–19 were exposed to 100 mg BPAF/kg/day by oral gavage. On the day of birth (postnatal day (PD) 0), cross-fostering took place between treated and control litters, and cross-fostered mother rats were given BPAF 100 mg/kg/day during the postnatal period (PD 3 to PD 19). HPLC-MS/MS analysis showed that BPAF was transferred via cord blood and lactation, finally bio-accumulating in the offspring testes. Pups exposed to BPAF both prenatally and postnatally showed a significant increase in testis testosterone levels compared with that of the control, while all pups exposed to BPAF showed a significant decrease in testis inhibin B (INHB) levels. Compared with the control, RNA-seq revealed that 279 genes were significantly differentially expressed in the testes of pups exposed to BPAF both prenatally and postnatally, including genes involved in cell differentiation and meiosis. These results indicate that gestational and lactational exposure to BPAF in the mother can impair reproductive function in male offspring. Highlights: Bisphenol AF bioaccumulated in offspring testes via cord blood and lactation. Pups exposed to BPAF showed significant increase in testis testosterone levels. 279 differentially expressed genes were identified in pup testes exposed to BFAF. Gene expression between two adjacent germ cell types was disrupted by BPAF.